Bahasa dan Pendidikan Karakter Dalam Pandangan Ki Hadjar Dewantara (Perspektif Teori Kritis Habermas) - Acetylena, Sita (AL-WIJDÃN Journal of Islamic Education Studies, 2018)
Resistance Ki Hadjar Dewantara in pioneering independence through a political movement or through character-based education is done by making the language as a fulcrum ofpengthe strugglemotion. Language is used as a tool to instill national character and language as a means to achieve independence discourse. Therefore, the purpose of this research is to know and understand Ki Hadjar Dewantara thinking about language and character education in view of Critical Theory Habermas. Habermas critical theory is a critical theory of communicative paradigm. In addition, to know how the language and character education undertaken Ki Hadjar Dewantara affects the movement's struggle for independence in Indonesia so as to become a sovereign state and is able to align with other nations in the world. Language and Character Education by Ki Hadjar Dewantara is very substantial for the existence and civilization of a nation. Speaking of character education the existence of a nation that is sovereign, independent, and self-sufficient should be based on a solid spiritual foundation that is reflected in the values of the character of the nation, especially character "independent physically and mentally", which with the true freedom can be realized. The cultural action carried out by Ki Hadjar Dewantara is not only critical discourse and arguments there but it can be said Ki Hadjar Dewantara's communicative action is called spiritual discourse. Dirkursus is called a spiritualist who for all communicative action, Ki Hadjar Dewantara both in education in the Park students and the people of Indonesia always based on spirituality. Thus, character education Taman Siswa which can be thought of as Ki Hadjar Dewantara is a true cultural action with one way that spiritual discourse. Keywords: Language, Character Education, Ki Hadjar Dewantar, Critical Theory Habermas